From Poverty to Perversity: Ideas, Markets, and Institutions over 200 Years of Welfare Debate - Somers, Margaret R.; Block, Fred (American Sociological Review, 2005)
To understand the rise of market fundamentalism from the margins of influence to mainstream hegemony, we compare the U.S. 1996 Personal Responsibility and Work Opportunities Reconciliation Act and the English 1834 New Poor Law—two episodes in which existing welfare regimes were overturned by market-driven ones. Despite dramatic differences across the cases, both outcomes were mobilized by “the perversity thesis”—a public discourse that reassigned blame for the poor's condition from “poverty to perversity.” We use the term “ideational embeddedness” to characterize the power of such ideas to shape, structure, and change market regimes. The success of the perversity thesis is based on the foundations of social naturalism, theoretical realism, and the conversion narrative. In the poverty to perversity conversion narrative, structural blame for poverty is discredited as empiricist appearance while the real problem is attributed to the corrosive effects of welfare's perverse incentives on poor people themselves—they become sexually promiscuous, thrust aside personal responsibility, and develop longterm dependency. This claim enables market fundamentalism to delegitimate existing ideational regimes, to survive disconfirming data, and to change the terms of debate from social problems to the timeless forces of nature and biology. Coupling economic sociology with a sociology of ideas, we argue that ideas count; but not all ideas are created equal. Only some have the capacity to fuel radical transformations in the ideational embeddedness of markets.